The Effect of Adding Iron Powder as an Additive to Rigid Pavement Concrete - Harahap, Winson Enrique; Wiyono, Sugeng; Elizar, Elizar (Jurnal Ilmu Dan Rekayasa Sipil, 2024)
On every construction project which using reinforced concrete there always any waste materials be in the form of iron scrap that can not be used. The iron materials that can not be used turn in to waste construction (waste materials). This research intend to know the influence of iron powder utilization as aditif for rigid pavement concrete and to application packing density concept that was used on a Ultra High Performance Concrete (UHPC). This research uses study experimental methods, starting from material properties test, mix design, concrete mix making, and flexural strength test implemented in Laboratorium Divisi Teknik PT. Lutvindo Wijaya Perkasa Pekanbaru. The research analysis is performed by comparing flexure strength test results of concrete without iron substitution with concrete substitution by iron powder. From this research are known flexure strength tests the concrete with 3% iron powder substitution has the highest flexure strength, which is 5.447 MPa. So from the results of this research, it can be concluded that the optimum addition of iron powder is 3%. The addition of iron powder can be a form of application of the concept packing density nano technology that has been applied to UHPC concrete, to obtain maximum density in concrete and increase concrete strength. It is also recommended to vary the size of the iron powder in future research so that the optimal iron powder size can be used as an additive.